THE POSSIBLE CONSEQUENCES OF TEACHERS' TYPES OF FORGIVENESS ON SCHOOL ORGANISATION - Berrin Burgaz; Sibel Bakan (Informascope, 2015)
The aim of this research is to find out primary school teachers' types of forgiveness and to discuss organisational reflections of these types. The research is based on a qualitative study. The selection of participants is based on the criterion sampling method which is categorized under purposive sampling. The data for this research was obtained through interviews with five teachers working in the same school. The data from these interviews was categorised into 20 case studies. Data is analysed by descriptive analysis. The results show that teachers totally forgive students, parents and other teachers whereas they do not forgive school managers.